2020
DOI: 10.1016/j.indag.2019.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Strong cliques and forbidden cycles

Abstract: Given a graph G, the strong clique number ω 2 (G) of G is the cardinality of a largest collection of edges every pair of which are incident or connected by an edge in G. We study the strong clique number of graphs missing some set of cycle lengths. For a graph G of large enough maximum degree ∆, we show among other results the following:These bounds are attained by natural extremal examples. Our work extends and improves upon previous work of Faudree, Gyárfás, Schelp and Tuza (1990), Mahdian (2000) and Faron a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 11 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…Note that this is tight as equality holds for the same graph demonstrating the tightness of Conjecture 2. It was recently revealed that forbidding all odd cycles is not necessary, as Cames van Batenburg, Kang, and Pirot [6] showed that a C5‐free graph G has strong clique index at most normalΔMathClass-open(GMathClass-close)2. This enhancement verifies the strong clique version of Conjecture 3, as well as Conjecture 4 with a much better upper bound.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Note that this is tight as equality holds for the same graph demonstrating the tightness of Conjecture 2. It was recently revealed that forbidding all odd cycles is not necessary, as Cames van Batenburg, Kang, and Pirot [6] showed that a C5‐free graph G has strong clique index at most normalΔMathClass-open(GMathClass-close)2. This enhancement verifies the strong clique version of Conjecture 3, as well as Conjecture 4 with a much better upper bound.…”
Section: Introductionmentioning
confidence: 75%
“…Cames van Batenburg, Kang, and Pirot [6] also considered the class of graphs with other forbidden odd cycles. They proved that a C3‐free graph G has strong clique index at most 1.25normalΔMathClass-open(GMathClass-close)2, which is tight for blowups of C5.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that this is tight as equality holds for the same graph demonstrating the tightness of Conjecture 2. It was recently revealed that forbidding all odd cycles is not necessary, as Cames van Batenburg, Kang, and Pirot [5] showed that a C 5 -free graph G has strong clique number at most ∆(G) 2 . This enhancement verifies the strong clique version of Conjecture 3, as well as Conjecture 4 with a much better upper bound.…”
Section: Introductionmentioning
confidence: 99%